Keterlibatan Orang Tua dalam Proses Asesmen Anak dengan Autisme - Akram, Hafizhul; Sri Nurhayati Selian (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to explore parental involvement in the assessment process for children with autism and to understand their experiences, roles, and challenges. The study used a qualitative approach with a phenomenological design involving three parents of children with autism who had undergone assessment by professionals. Data were collected through in-depth interviews, observation, and documentation, then analyzed using thematic analysis. The results revealed five main themes: parents' initial awareness of their child's developmental differences, their role in providing developmental information, emotional experiences during the assessment process, the benefits of the assessment in improving understanding of the child's needs, and challenges faced during the process. The findings indicate that parental involvement significantly contributes to enriching assessment information and improving understanding of the child's condition, despite facing various barriers such as limited knowledge, time, cost, and emotional aspects. This study concludes that a family-centered approach is crucial in the assessment process. Therefore, stronger collaboration between professionals and parents is needed to support the optimal development of children with autism.